Degradation behavior of pure Mg in the physiological medium and growth mechanism of surface corrosion product films - Chenyu Wang; Mingshan Sun; Chao Yang; Haiyang Wang; Jie Wang; Lin Mao; Yao Yang; Tao Ying; Paul K. Chu; Xiaoqin Zeng (Journal of Magnesium and Alloys)
Pure Mg boasting a relatively small corrosion rate is a potential biodegradable metal material for implants. However, its degradation behavior in the complex physiological environment is still a lack of understanding. In this work, we investigated the effect of corrosion product film layers on the degradation behavior of pure Mg in physiological environments. Pure Mg shows a faster corrosion rate in simulated body fluid (SBF) compared to NaCl solution. Hydrogen evolution experiments indicate that the degradation rate of pure Mg in SBF decreases rapidly within the first 12 h but stabilizes afterward. The rapid deposition of low-solubility calcium phosphate on the pure Mg in SBF provides protection to the substrate, resulting in a gradual decrease in the degradation rates. Consequently, the corrosion product film of pure Mg formed in SBF exhibits a layered structure, with the upper layer consisting of dense Ca3(PO4)2/Mg3(PO4)2 and the lower layer consisting of Mg(OH)2/MgO. Electrochemical impedance spectroscopy (EIS) shows that the resistance of the corrosion product film increases over time, indicating gradual strengthening of the corrosion resistance. The 4-week degradation results in the femoral marrow cavity of mice are consistent with the result in SBF in vitro.